Scientific and theoretical foundations of cooperative pedagogy and its role in the modern education system - BOBOEYEVA SABINAKHAN LAZIZ KIZI (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2026)
One of the important requirements for today's teachers and educators, especially professors working in higher education institutions, is to teach young people to think independently by deeply understanding and applying innovations in the field of education. Knowing the essence and ideas of cooperative pedagogy is also one of these requirements.